Nurse Scheduling Optimation with Various Assignment Pattern at ABC Hospital Using Goal Programming Method - Sigit Ananda Murwato; Abdullah Shahab (IPTEK Journal of Proceedings Series, 2020)
In fulfilling health services in hospitals, the availability of human resources (HR) which includes doctors, nurses, midwives, and so on, plays a very important role. In terms of amount and dominant existence in the hospital in providing health services to patients is a nurse. The role of hospital management in maintaining the availability of nurses is to plan a good schedule. Without a good resource scheduling plan, the services will not be optimal and the costs will hard to control. This research aims to optimize the nurse scheduling. Existing schedule did not pay attention to specific time that have different load to another. Management feels that a lot of idle time is experienced by some nurses. Therefore, from the data that occurred in the past there will be observations that every 4 hours will occur how many services performed and how many nurses needed. Furthermore, by using Goal Programming method, several priority objectives are made, such as how to minimize the deviation of nurses needed in one shift or slot. Then how to minimize the excess target number of nurses who work in one week. And then minimize the excess number of nurses who work on the night shift. The suggested mathematical model has been implemented using Lingo Software. Work patterns have been suggested to improve schedules quality based on different load of services that occur in specific time. The suggested approach can be used for any similar staff scheduling problem in the next research.